Politik Anggaran Desa: Keberpihakan Pemerintah Desa terhadap Pengembangan Pemuda Karang Taruna dalam APB Desa Kedungturi Kecamatan Taman Kabupaten Sidoarjo Tahun Anggaran 2018 dan 2019 - Ibnu Arifin, Nur Zaid (Prodi Ilmu Politik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Islam Negeri Sunan Ampel Surabaya, 2023)
The purpose of this research is to find out how the political conformation of the budget provided by the Kedungturi Village Government’s towards the development of youth through the Village Budget in 2018 and 2019. This research uses a type of literature study research using budget political theory initiated by Wildavsky. The results of this study found a political conformation of village government budget towards the development of cadet reef youth in the Village Budget Year 2018 and 2019, with a budget allocated of Rp 53,579,467 in 2018 and Rp 76,669,000 in 2019. According to Wildavsky's budget theory, sharing and bargaining is necessary in the process of making a policy. In the process of formulating APB Desa is carried out together through village musrenbang forum. Where village governments and communities meet and there is room to express opinions so that there is a process of sharing and bargaining. If demanded from the beginning, the partiality towards the development of youth coral cadets begins from the Village RPJM in 2014-2019 which is a reference in preparing the document RKP and Village APB annually as well as programs that refer to the annual work program. The village government's partiality towards the development of youth coral cadets is a must do to prepare future generations who have skills and abilities that can bring progress for themselves and the progress of the village.